Middle school general music : the best part of your day - McAnally, Elizabeth Ann; National Association for Music Education (Lanham : Rowman & Littlefield, 2016)
Middle School General Music: The Best Part of Your Day is a superbly written guide for educators who seek to equip adolescents with the skills and competencies that will give them a lifelong appreciation of music and music making. Supported by scholarly research, this volume by Elizabeth Ann McAnally successfully makes the case for general music as a core and essential subject at the middle school level. McAnally notes that general music experiences can play a role in both brain and identity development during the adolescent years. With respect to the National Core Arts Standards, the author offers strategies and techniques for the processes of creating, planning, making, evaluating, refining, presenting, performing, selecting, analyzing, interpreting, responding to, and connecting with music. For each standard, McAnally offers practical activities and projects that are relevant to the lives of adolescents. Each lesson is well-designed and skillfully sequenced; they all clearly reflect the real-life experiences of the author. McAnally successfully provides the reader with suggestions for connecting music with other subjects, including reading, writing, science, mathematics, social studies, other arts disciplines, and daily life. This book is an invaluable guide for educators who wish to make general music an accessible, engaging, and relevant experience for adolescents. The lessons provided in this resource are guaranteed to enhance the musical, creative, collaborative, and critical thinking skills of young people of all backgrounds. - Foreword.
Foreword / Rollo Dilworth -- Introduction : Why middle school general music? -- Creating -- Performing -- Responding -- Connecting -- Appendixes. Activities to strengthen notation skills -- Tips for working with adolescents -- Resources -- References -- About the author.
"Published in Cooperation with the National Association for Music Education."
Includes bibliographical references (pages 153-154).
Keywords: School music -- Instruction and study -- Outlines, syllabi, etc; School music -- Instruction and study -- Handbooks, manuals, etc